Self-assembly of di(pyrazol-1-yl)pyridine-benzoic acid on underpotentially deposited Ag from solution - Aitchison, Hannah; Ortiz de la Morena, Rodrigo; Peifer, Raphael; Omar, Suhad; Lu, Hao; Francis, Stephen M.; Zharnikov, Michael; Grohmann, Andreas; Buck, Manfred (Langmuir, 2018)
Monolayers of 4-(2,6-di(1H-pyrazol-1-yl)pyridine-4-yl)benzoic acid (DPP-BA) on Au substrates modified by an underpotential-deposited bilayer of Ag were studied by X-ray photoelectron spectroscopy (XPS), near edge X-ray absorption fine structure spectroscopy, and scanning tunneling microscopy. Highly crystalline layers are formed with molecules coordinatively bonding to the surface through the carboxylate moiety in a bidentate configuration. The molecules assemble to rows characterized by densely packed upright-orientated DPP units occupying an area of 41 Å2. The DPP units adopt a trans-trans conformation as inferred from the N 1s XPS spectra taken at different photon energies. Their alignment alternates between adjacent rows, giving rise to a herringbone pattern. The pronouncedly different structure of the weakly commensurate self-assembled monolayer (SAM) of DPP-BA on Ag compared to the commensurate SAM of a DPP thiol on Au is a manifestation of the shift from substrate-directed assembly in the latter case to assembly dominated by intermolecular interactions in the former case.